High prevalence of psychiatric disorders in patients with skin‐restricted lupus: a case–control study4. (27th March 2016) - Jalenques, I.; Rondepierre, F.; Massoubre, C.; Haffen, E.; Grand, J.P.; Labeille, B.; Perrot, J.L.; Aubin, F.; Skowron, F.; Mulliez, A.; D'Incan, M.; ,
Summary: Background: Psychiatric disorders have been extensively documented in patients with systemic lupus erythematosus (SLE). However, the prevalence of psychiatric disorders in patients with skin‐restricted lupus (SRL) remains unknown, although SRL is more common than SLE. Objectives: To assess current and lifetime prevalence of Axis I psychiatric disorders among outpatients with SRL and to examine the factors associated with psychiatric disorders among such patients. Methods: A multicentre case–control study involving outpatients with SRL and controls matched for sex, age and education level. The Mini International Neuropsychiatric Interview was used for psychiatric evaluation. Results: We evaluated 75 patients and 150 controls. Of these, 49% of patients vs. 13% of controls fulfilled the criteria for at least one current psychiatric disorder ( P < 0·001). The following disorders were significantly more frequent among patients than controls: current and lifetime major depressive disorder (9% vs. 0%, P < 0·001 and 44% vs. 26%, P = 0·01), generalized anxiety disorder (23% vs. 3%, P < 0·001 and 35% vs. 19%, P = 0·03), panic disorder (7% vs. 0%, P = 0·004 and 21% vs. 3%, P < 0·001), current suicide risk (24% vs. 7%, P = 0·003), alcohol dependence (7% vs. 0%, P = 0·004) and lifetime agoraphobia (20% vs. 9%, P = 0·01). Lupus duration and lupus past treatment by thalidomide were significantly higher among patients with current psychiatric disorders. Conclusions: This study demonstrates a high prevalence of several psychiatric disorders (anxiety, depression, suicide risk, alcohol dependence) in patients with SRL. Abstract : What's already known about this topic? No data exist about psychiatric disorders in patients with skin‐restricted lupus (SRL). What does this study add? Patients with SRL have a high prevalence of current and lifetime major depressive disorder, generalized anxiety disorder and panic disorder, current suicide risk, alcohol dependence and lifetime agoraphobia. Patients with SRL often lack specialized mental health care. Linked Comment: Bewley. Br J Dermatol 2016;174 :958–959 Plain language summary available online